Strengthening Legal Awareness and Community Participation in Talaka Village Governance - Muhammad Fikri; Eka Merdekawati Djafar; Adrian; Sardil Mutaallif; Andi Budiman; Muhammad Fathir Al Farisi; Maulana Dafa Suwandi; A. M. Randy Syekh; A. Maisyah Amalia; Linda Sekar Sari; Athifah Putri Fidar; Ismi Azizah Djufri; A. Putra Alen Pratama; Vega Sampe Rompon; Zhairah Zulaeyka Imran (STMIK Indonesia Banda Aceh, 2026)
This community service activity aims to strengthen the governance of Talaka Village through the application of good governance principles by increasing legal awareness and community participation. The problem faced is the incompatibility between the ideal norm of public participation as stipulated in laws and regulations and the reality in the field which is still formalistic and has minimal community involvement. To overcome these problems, the method used in this service is qualitative legal research with a Participatory Rural Appraisal (PRA) approach. The results of the service show that the practice of community participation in village governance is still administrative and symbolic, influenced by limited access to public information and weak communication mechanisms between apparatus and residents. Through PRA-based legal socialization, there is an increase in participant involvement in discussions, the growth of community legal awareness, and the opening of a more equal dialogue space between village officials and the community. Thus, this service contributes to strengthening the capacity of the apparatus and encouraging the creation of more participatory, transparent, and sustainable governance at the local level.